Here's to you, Rachel Robinson - Blume, Judy (New York Orchard Books, 1993)
Expelled from boarding school, Charles' presence at home proves disruptive, especially for sister Rachel, a gifted seventh grader juggling friendships and school activities
1
Keywords: Brothers and sisters -- Fiction; Family problems -- Fiction; Friendship -- Fiction; Gifted children -- Fiction